2020
DOI: 10.1186/s12884-020-02906-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of some social and clinical factors on the development of postpartum depression in Chinese women

Abstract: Background: Postpartum depression (PPD) is prevalent and may present major adverse impacts on mother and child health. According to previous studies, mostly from the western society, PPD may have complicated etiologies, such as genetic, social and psychological factors. The aim of this study was to explore the associations of some social and clinical factors, particularly those unique in Chinese, with significant PPD symptoms. Methods: A sample of 556 pregnant women in their 36th to 40th gestational week were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
22
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 20 publications
5
22
2
2
Order By: Relevance
“…In our study, one of the most important factors in the development of postpartum depression symptoms was Cesarean delivery. Other studies support this thesis [ 40 , 41 ]. It may be related to the greater limitations than after natural childbirth, pain at the site of the surgical wound, or delayed lactation.…”
Section: Discussionsupporting
confidence: 77%
“…In our study, one of the most important factors in the development of postpartum depression symptoms was Cesarean delivery. Other studies support this thesis [ 40 , 41 ]. It may be related to the greater limitations than after natural childbirth, pain at the site of the surgical wound, or delayed lactation.…”
Section: Discussionsupporting
confidence: 77%
“…Strong social support leading to lowest and poor Social Support to highest PPD levels delineated the precedence of social support in mediating the risk factors for PPD. These results supporting previous research suggests that intensive and negative involvement of relatives in a participant's life and lack of support from husband were strongly associated with significant PPD symptoms 15 . Also, previous research on rural samples establishes the importance of partner's support 16 ; social support is also the best intervention strategy to lower PPD 17 .…”
Section: Discussionsupporting
confidence: 91%
“…Our focus on probable as well as suspected PPD is a strength of the study because it broadens the group that may benefit from interventions to reduce PPD. In two previous cohort studies in China, 9‐point thresholds were used to determine the risk of PPD and to explore the risk factors of PPD (Li et al, 2020; Song et al, 2018). These authors identified lower prevalence rates of 17% (Li et al, 2020) and 8.5% (Song et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In two previous cohort studies in China, 9‐point thresholds were used to determine the risk of PPD and to explore the risk factors of PPD (Li et al, 2020; Song et al, 2018). These authors identified lower prevalence rates of 17% (Li et al, 2020) and 8.5% (Song et al, 2018). Other studies in China that used the threshold of 13 identified the lower prevalence of PPD of 27% (Deng et al, 2014) and 23% (Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%